Electrical modulation of the sympathetic nervous system in order to augment cerebral blood flow: a protocol for an experimental study - J Marc C van Dijk (BMJ Open)
Introduction Cerebral blood flow (CBF) is regulated by several mechanisms. Neurogenic control has been a matter of debate, even though several publications reported the effects of changes in sympathetic tone on CBF. Transcutaneous electrical nerve stimulation and spinal-cord stimulation have been shown to influence peripheral and cerebral blood flow through a sympathetic pathway. The authors hypothesise that certain pathological conditions result in a relative increase in the neurogenic regulation of CBF and that this regulation can be modulated electrically.Methods and analysis Patients with cerebral vasospasm after subarachnoid haemorrhage will be included. The experimental set-up measures several parameters that are involved in cerebral blood flow regulation in patients with cerebral vasospasm after subarachnoid haemorrhage. Measurements are taken at baseline and with stimulation in several frequencies. An ad hoc statistical analysis is used to evaluate different settings of the electrical stimulation. Autoregulation is evaluated with transfer function analysis and autoregulatory index calculations.Ethics and dissemination Ethical registration was granted by Medical Review Ethics Committee Groningen (ID METc 2010.123). All participants provide written informed consent on participation. Upon finishing a pilot study to investigate feasibility and effect, either future prospective (randomised) studies will be designed, or other modalities of electrical stimulation will be explored using the same set-up.Trial Registration Dutch Trial Registry: NTR2358.